Iot-Based Smart Medicine Dispenser: A Technological Solution for Medication - Abhijith M, Abhijith M; Aadith S, Aadith S; Kumari Gond, Anshu; Krishna G, Krishna G; Dhanasri G, Dhanasri G; Bhavani, Bhavani; K. Selvavinayaki, K. Selvavinayaki (Journal of Neonatal Surgery, 2025)
Medication adherence is a significant challenge, especially among elderly and chronically ill patients. This paper presents an IoT-based Smart Medicine Dispenser (SMD) designed to automate and optimize medication management. The system incorporates an ESP32 microcontroller, Arduino, IR sensors, and a web-based interface to ensure timely and accurate medication dispensing. The integration of IoT technology enables remote monitoring, providing caregivers with real-time adherence data. The paper discusses the system's hardware and software components, implementation methodology, and potential impact on healthcare outcomes. The findings suggest that the SMD enhances medication adherence, reduces human errors, and improves patient independence...